Beneficial Effect of Altruism on Well-Being Among Chinese College Students: The Role of Self-Esteem and Family Socioeconomic Status. Issue 43 (27th May 2017) - Feng, Linlin; Guo, Qingke
ABSTRACT: The motivation for voluntary social service has been identified as altruism. This study aimed to establish the relationship between altruism and well-being in Chinese college students at the undergraduate level. To better understand altruism, two groups were selected, one that used self-reporting and another related to the perception of peers. Self-reported altruism and self-reported decisions to help in real-life situations were measured in the first sample ( N 1 = 525); peer-rated altruism was measured in the second sample ( N 2 = 189). The results showed (when socially desirable responding was controlled) (1) self-reported altruism and self-reported decisions to help exerted significant direct effects on well-being, while peer-rated altruism did not; (2) self-esteem mediated the effects of self-reported altruism, self-reported decisions to help, and peer-rated altruism on well-being; (3) family socioeconomic status moderated the effects of self-reported altruism on well-being via self-esteem; college students with low family socioeconomic status were more likely to reap benefits from altruism. These findings confirm the emotion-elevating effects of altruism in collectivistic societies like China, which may encourage more people to engage in voluntary social service. Future research should adopt longitudinal or experimental designs with a more nationally representative sample to better confirm these findings.